Optimization of Velocity in Heat Exchanger Networks for Fouling Mitigation - S. Zhan; Y. Wang; X. Feng (Chemical Engineering Transactions, 2015)
Fouling severely reduces energy recovery in heat exchanger network (HEN). Low velocity and high wall temperature are the reasons for a high fouling rate. Redistribution of velocity for the exchangers in the network is an efficient way to mitigate fouling. In this work, optimizing the velocity distribution through the network is considered to correlate heat transfer, pressure drop and fouling. Two ways are used to change the velocity in each heat exchanger. They are modifying detailed heat exchanger structure and redistributing flow rates in the two exchangers in parallel. Additionally, after redistributing flow rate in the two heat exchangers in parallel, the temperature of them is also changed due to the change in heat capacity flow rate. To describe the dynamic nature of fouling, the entire time zone is divided into several time intervals. Fouling resistance is used to link the two adjacent intervals. To optimize the heat exchanger network with comprehensive considerations of the above motioned factors, a methodology is proposed. A crude oil preheat train is used to verify the validity and efficiency of the proposed approach.